A Study on Brain Fingerprinting Technology - Deepika, S.; Kaviyadharshini, B.; Sharmila, S.; Sangeethaa, S. N.; Jothimani, S. (Journal of Ubiquitous Computing and Communication Technologies, 2022)
The detection and resolution of any crime is made possible with the use of modern technology. The crime is discovered, the suspect is named, and then the court is presented with sufficient proof to show that the crime was committed by the named suspect. The proofs could be mental or physical. The best lie detector now in existence, according to this invention, is reported to be able to catch even sneaky crooks who successfully pass the standard polygraph test. Criminal investigators gather physical evidence, which can be destroyed, while mental evidence is preserved in the brain and cannot be erased. The brain wave reaction of an individual to crime-related images or phrases displayed on a computer screen can be used to analyze those evidences, using Electroencephalography (EEG). This novel Brain Fingerprinting technique uses brainwaves, which can be used to determine if the test participant remembers the specifics of the incident. The brain wave issuer will trap him even if they are consciously hiding the required information. Over 120 studies, including testing on Federal agents, testing for the United States intelligence agency and the US Navy, tests on actual cases, including felony crimes, have demonstrated that brain fingerprinting is 100 percent accurate.
Keywords: Brain fingerprint technology; electroencephalography (EEG); crime; brain wave response